Interactive Simulation on Modern Physics: A Systematic Review: A Systematic Review - Candido, Keneth John O.; Gillesania, King Christian C.; Mercado, Justine C.; Reales, Joy Mae B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Physics is a theoretical science, understanding the concepts requires actual visual representations and models. Physics instructors should teach physics using inquiry, discovery, demonstration, simulation, practical work, lab-based activities, and other practical experiences. The current status of knowledge and practice regarding interactive simulation in the teaching of modern physics is presented in this systematic literature review. By methodically evaluating and summarizing the most pertinent previous research publications published from December 2002 to January 2022, it offers guidance for instructional designers and scholars. After careful consideration and screening, a total of eleven studies were chosen for a thorough analysis and synthesis. The results showed that the objective of the research studies on using interactive simulation in modern physics is to enhance students' critical thinking skills and creative problem-solving skills. It has been demonstrated that interactive simulation technologies like Java applets and Physics Education Technology (PhET) are successful at teaching modern physics. The success or failure of employing interactive simulation is influenced by teachers, school staff, students, simulation design, and technology used. The findings imply that educational institutions should provide teachers and administrators with tutorials and training, and this review recommend that the interactive simulation should be available and that a gadget-friendly simulation must be developed.